2022
DOI: 10.1002/humu.24383
|View full text |Cite
|
Sign up to set email alerts
|

The fibrillinopathies: New insights with focus on the paradigm of opposing phenotypes for both FBN1 and FBN2

Abstract: Different pathogenic variants in the fibrillin-1 gene (FBN1) cause Marfan syndrome and acromelic dysplasias. Whereas the musculoskeletal features of Marfan syndrome involve tall stature, arachnodactyly, joint hypermobility, and muscle hypoplasia, acromelic dysplasia patients present with short stature, brachydactyly, stiff joints, and hypermuscularity. Similarly, pathogenic variants in the fibrillin-2 gene (FBN2) cause either a Marfanoid congenital contractural arachnodactyly or a FBN2-related acromelic dyspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 141 publications
0
13
0
Order By: Relevance
“…The diagnosis of CCA is established with suggestive findings and heterozygous FBN2 pathogenic variants identified by molecular testing [ 2 ]. However, fibrillin genes variants shows various clinical phenotype without marfanoid features or classical features without FBN2 gene mutation [ 5 ]. Especially, the occurrence of FBN2 related disorder make it more difficult for it to be diagnosed because some of the features either improve or are overlooked in infant, thus, the need to prove the FBN2 mutation is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of CCA is established with suggestive findings and heterozygous FBN2 pathogenic variants identified by molecular testing [ 2 ]. However, fibrillin genes variants shows various clinical phenotype without marfanoid features or classical features without FBN2 gene mutation [ 5 ]. Especially, the occurrence of FBN2 related disorder make it more difficult for it to be diagnosed because some of the features either improve or are overlooked in infant, thus, the need to prove the FBN2 mutation is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In developmental lung, FBN2 occurs earlier and is a stronger inducer of elastin synthesis than FBN1, furthermore, it is buried within the postnatal microfibrils and may be unrecognized in the postnatal period [ 12 ]. Fibrillin also regulates transforming growth factor -β(TGF-β)by sequestration of the extracellular matrix, through binding to other protein such as the latent TGF-β binding proteins 4 (LTBP-4) [ 5 ]. Elevated LTBP-4 has previously been reported in PPFE patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this paediatric cohort, 5% of patients harboured a pathogenic CNV in FBN1 . FBN1 encodes fibrillin-1 that functions as a structural component in the extracellular matrix and regulates growth factor signalling pathways [ 20 ]. A study by Yamaguchi et al [ 21 ] identified one multiexon deletion of COL3A1 (alpha 1 chain of type III collagen) in a patient with vascular Ehlers-Danlos syndrome (vEDS; MIM #130050).…”
Section: Introductionmentioning
confidence: 99%
“…FBN1 plays an important role in the stability and strength of these tissues 8 . Microfibril production is disrupted by pathogenic FBN1 variants, which also cause abnormal fibrillin protein formation and ultimately impair connective tissue 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 Microfibril production is disrupted by pathogenic FBN1 variants, which also cause abnormal fibrillin protein formation and ultimately impair connective tissue. 9 Here, we characterized the phenotype and determined the genetic etiology of a large Iranian family with symptoms consistent with MFS using molecular diagnostic methods. Through whole exome sequencing (WES) and bioinformatics analysis, a heterozygous missense pathogenic variant (c.2179T>C) in FBN1 gene was detected in the proband and affected family members.…”
Section: Introductionmentioning
confidence: 99%